ePoster: Lovely.Love.App / Nor Aishah Jalal, Izzmadihah Mohamad Supian, Nur Fazziatul Aqma Hashim and Raja Nur Aini Hidyah Raja Hassan - Jalal, Nor Aishah; Mohamad Supian, Izzmadihah; Hashim, Nur Fazziatul Aqma; Raja Hassan, Raja Nur Aini Hidyah (2022)
Considering Covid 19 cases are declining worldwide, the tourism and hospitality industry in certain countries has opened borders. It make more demand for such as services, so our app is one of the services for covid 19 pandemic is declining to facilitate consumers. The concepts in this app will make it easier for users out there to plan, find ideas and inspiration to start their honeymoon journey. They can find the best hotels and interesting tour packcage to visit. Not the same as most other apps because this app is more focused on couples who want to enjoy a private honeymoon. This application also does not require a cost to use it unless the couple wants to book the travel package offered. This application collaborates with many other travel agencies to make it easier for couples to choose the desired honeymoon place.